Orally administered mixed carotenoids protect human skin against ultraviolet A‐induced skin pigmentation: A double‐blind, placebo‐controlled, randomized clinical trial - Baswan, Sudhir M.; Marini, Alessandra; Klosner, Allison E.; Jaenicke, Thomas; Leverett, Jesse; Murray, Mary; Gellenbeck, Kevin W.; Krutmann, Jean (Photodermatology, photoimmunology & photomedicine, 2020)
Background Photoprotection of human skin is determined as the capacity of sunscreens to prevent ultraviolet (UV) B radiation‐induced erythema and UVA radiation‐induced pigmentation. It is unequivocal that, in addition to sunscreens, oral supplementation with carotenoids can protect human skin against UVB radiation‐induced erythema. It is not known if this is also the case for UVA radiation‐induced pigmentation. Objective To clinically evaluate the photoprotective effects of daily supplementation with carotenoids against UVA radiation‐induced pigmentation. Methods In this double‐blind, placebo‐controlled trial, 60 subjects (Fitzpatrick types II‐IV) were randomized to receive Nutrilite™ Multi Carotene supplement or placebo for 12 weeks. UVB‐induced minimal erythemal dose (MED), UVA‐induced minimal persistent pigmentation dose (MPPD) and skin carotenoid levels were measured at baseline, 4, 8, and 12 weeks of intervention. Skin color was evaluated by expert clinical graders and by colorimetry. Carotenoid levels in the skin were measured by the Biozoom® device. Results In the intervention group, a significant increase in comparison with the placebo group was observed in (a) skin carotenoid levels, (b) UVB‐induced MED, and (c) UVA‐induced MPPD values obtained by colorimetry. Conclusion Daily supplementation with carotenoids protects human skin against both UVB‐induced erythema and UVA‐induced pigmentation.